Stereotip Karakter Perempuan dalam Buku Ajar untuk Sekolah Dasar: Kajian Multimodalitas - Fadhila Yonata; Yoniswan Yoniswan (Jurnal Bahasa dan Sastra, 2021)
Myriads of studies about gender stereotypes in educational materials have been carried out by global scholars in recent years. One of the focus is in the textbook seems to be crucial due to its prominent role as guidance to curriculum and teachers’ credence on the contents. A textbook actually has two important role as vehicle of knowledge transfer and of social practices paradigm construction. However, little studies have reported on the representation of female characters stereotypes in the context of elementary school language textbook. Following multimodality framework proposed by Van Leuween (2008), verbal and visual texts in two English language textbooks published by private companies in Indonesia were analysed in respect to gender stereotyped. The findings reveal the existence of stereotypes of female character on personality, hobby and interest, occupation, and social roles. The study suggests textbook makers (authors and publishers) and users (parents, teachers, and education stakeholders) to rise critical gender awareness.